Isolation of Primary Brain Cells: Challenges and Solutions - Aggarwal, Arnav; Mendoza-Mari, Yssel; Aggarwal, Anshu; Agrawal, Devendra K. (Archives of Clinical and Biomedical Research, 2025)
The isolation of primary brain cells is essential for studying cellular behavior, signaling pathways, and disease mechanisms in the central nervous system. This paper explores the general and specific steps involved in extracting and culturing neurons, astrocytes, and microglia from brain tissue, highlighting how primary cells maintain their functionality and structural integrity without genetic modification like immortalized cell lines. Marker proteins such as MAP-2, GFAP, IBA-1, and TMEM119 help confirm cell identity and allow tracking of phenotypic changes, such as inflammation or maturation. We critically discussed some technological problems that researchers usually face during extraction and culturing procedures, emphasizing that each brain source and particular cell type require strict conditions to maximize cellular yield and viability. Environmental control of the cells in culture, such as pH, CO2, substrate coating and correct medium formulation, are critical for maintaining healthy and viable brain cell cultures. Limited lifespan and sensitivity of primary neurons restrict long-term experiments and increase the risk of experimental variability. Batch-to-batch variation in tissue sources leads to inconsistency in phenotype and function, especially with primary cell isolations. Ethical and practical limitations in sourcing human brain tissue reduce the generalization of findings and force reliance on clinically relevant experimental animal models that represent human conditions.